Oral Manifestations of Human Immunodeficiency Virus Infection - Epstein, Joel B. (1988)
The AIDS epidemic continues. All health-care workers, including physicians and dental personnel, may be instrumental in recognizing risk factors associated with Acquired Immunodeficiency Syndrome (AIDS) and Human Immunodeficiency Virus (HIV) infection. Oral signs and symptoms of HIV infection may be the first presentation of the disease or may develop during the course of the disease and require management. Knowledge of the signs, symptoms and associated infections and tumours is needed to assist in recognition, diagnosis, and treatment.